Development of a potent 2-oxoamide inhibitor of secreted phospholipase A2 guided by molecular docking calculations and molecular dynamics simulations. Issue 8 (15th April 2016) - Vasilakaki, Sofia; Barbayianni, Efrosini; Leonis, Georgios; Papadopoulos, Manthos G.; Mavromoustakos, Thomas; Gelb, Michael H.; Kokotos, George
Graphical abstract: Abstract: Inhibition of group IIA secreted phospholipase A2 (GIIA sPLA2 ) has been an important objective for medicinal chemists. We have previously shown that inhibitors incorporating the 2-oxoamide functionality may inhibit human and mouse GIIA sPLA2 s. Herein, the development of new potent inhibitors by molecular docking calculations using the structure of the known inhibitor7 as scaffold, are described. Synthesis and biological evaluation of the new compounds revealed that the long chain 2-oxoamide based on ( S )-valineGK241 led to improved activity (IC50 = 143 nM and 68 nM against human and mouse GIIA sPLA2, respectively). In addition, molecular dynamics simulations were employed to shed light onGK241 potent and selective inhibitory activity.